Question

Asked Dec 2, 2019

20 views

For the following functions, find (f*g)(3) (Enter an exact number.)

f(x)=x^2-8

g(x)=4x-5

Step 1

(f*g)(3)= f(3)*g(3)

We find f(3) by plugging x=3 in f(x).

f(3)=1

Step 2

We find g(3) by plugging x=3 ...

Tagged in

Find answers to questions asked by student like you

Show more Q&A

Q: I need help with practice question 11 only.

A: Plug x=0 in f(x). f(0)=0, then plug x=0 in g(x)Answer: 1

Q: 1)90% of adult females hace height h (in feet) that satisfies the inequality |h-5.35/0.21| ≤ 2 a)So...

A: The inequality is given by

Q: Algebra Question

A: Part a) To show that the function is one to one function.Part b) To find the inverse of the function...

Q: Combine the following rational expressions. 1 2x - 4 1 r2 x20 2+5 +4 a2- 4x- 5 TIP Enter your answer...

A: The given rational expression is,

Q: 35. Which equation represents the graph ofy= -|4xl translated down 1 unit and right units? X=S a. y=...

A: Click to see the answer

Q: Solve the system of nonlinear equations using substitution. y = −x x2 + y2 = 25 ...

A: Given that

Q: I am unable to figure out the last two parts of the questions

A: Click to see the answer

Q: Strontium 90 is a radioactive material that decays according to the function Upper A left parenthesi...

A: Given,A(t) = A0e-0.0244tHalf-life of the function is when,

Q: Simplify 2 b+3 1 1 b2 9 b-3 Preview E e 99+ thp LETT PACK ARD

A: Simply the expression.